Social responsibility of science - Kobylarek, Aleksander (Journal of Education Culture and Society, 2019)
This article tackles the problem of social involvement by academics and researchers. The author defines social responsibility widely as the involvement of knowledge, academics and educational institutions in solving the problems of the local community. The concept predicts that this can come about not only by disseminating research results, but also by involvement in pro-social activity without loss of autonomy. The author shows that this can be a way of building trust in science, as well as being a tool in opposing the anti-science culture. It can also be a means of rebuilding the status of science in a world of information bubbles and fake news.